Interrelationships Between Intimate Partner Violence, Coping Style, Depression, and Quality of Life Among the Regular Female Sexual Partners of Men Who Have Sex With Men - Yan, Fang (Journal of interpersonal violence, 2022)
The regular female sexual partners of men who have sex with men (MSM), namely, “Tongqi” in China, increasingly attract attention in the field of public health due to their high levels of depression and intimate partner violence (IPV), and their potential risk of HIV infection. Few studies have explored the relationships among IPV, coping style, depression, and quality of life (QOL) in this population. To examine these relationships, a cross-sectional online survey was conducted in China from February 2016 to March 2017. A questionnaire, including the Revised Conflict Tactics Scales, the Simplified Coping Style Questionnaire, the Center for Epidemiologic Studies Depression Scale, and the World Health Organization Quality of Life Scale, was completed by a total of 194 Chinese Tongqi. Structural equation modeling (SEM) was used to test the relationships among IPV, coping style, depression, and QOL. IPV (β = −0.12, p = .002), depression (β = −0.79, p < .001), and active coping style directly (β = 0.17, p < .001) affected the QOL of this group of women; IPV also indirectly affected QOL through the mediating effect of passive coping style and depression, and the positive coping style indirectly affected QOL through the mediating effect of depression. The proposed model showed good fit of indices, χ2/d = 43.72/34 = 1.286 < 3, p = .123, root mean square error of approximation (RMSEA) = 0.038. Chinese Tongqi experienced high levels of IPV, which led to a poor QOL, partially through the mediating role of passive coping strategy and depression. Future studies or interventions should emphasize the IPV experienced by Chinese Tongqi and provide psychological support so as to improve the overall well-being of this vulnerable female population.